ENTERPRISE MANAGEMENT IN THE CONTEXT OF EXPANDING THE SCOPE OF BLOCKCHAIN TECHNOLOGY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The method of creating an automated enterprise management system is considered. The method is based on the ideas of the imitation approach and fuzzy mathematics. Real-time enterprise planning is the goal. The method is relevant in the context of setting up the market for goods and services with the expansion of e-commerce. The model of the formation of the plan of the enterprise for the execution of the orders received is considered.